A Modified Multi-Step Crossover Fusion (MSXF) In Solving Some Deterministic Job Shop Scheduling Problem (JSSP) [TS157.5. M214 2008 f rb]. - Omar, Mahanim (2008)
This thesis addresses the job shop scheduling problem (JSSP) with the objective of minimising the makespan value.